2019
DOI: 10.1161/circulationaha.118.038362
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis of the Normal Mouse Aorta Reveals Functionally Distinct Endothelial Cell Populations

Abstract: Background-The cells that form the arterial wall contribute to multiple vascular diseases. The extent of cellular heterogeneity within these populations has not been fully characterized. Recent advances in single cell RNA-sequencing makes it possible to identify and characterize cellular subpopulations.Methods-We validate a method for generating a droplet-based single cell atlas of gene expression in a normal blood vessel. Enzymatic dissociation of four whole mouse aortas was followed by single cell sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
267
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(290 citation statements)
references
References 46 publications
22
267
0
1
Order By: Relevance
“…Current single-cell analysis has now addressed this limitation. We also compared our carotid endothelial gene expression data to the previously published endothelial heterogeneity data from murine ECs from various tissue types and arteries (Kalluri et al, 2019;Kalucka et al, 2020). While we found that most of the highly enriched genes (Fbln5,Mecom,Gja4,Azin1,Sox17,Mgp,Nrp1,Kcnj8,Cytl1,Bmx,Eln,Fbln2,Gkn3) found in the arteries were also present in all of our EC clusters showing no flow dependency.…”
Section: Accessibility and Co-accessibility Analyses Reveal Flow-depementioning
confidence: 72%
See 3 more Smart Citations
“…Current single-cell analysis has now addressed this limitation. We also compared our carotid endothelial gene expression data to the previously published endothelial heterogeneity data from murine ECs from various tissue types and arteries (Kalluri et al, 2019;Kalucka et al, 2020). While we found that most of the highly enriched genes (Fbln5,Mecom,Gja4,Azin1,Sox17,Mgp,Nrp1,Kcnj8,Cytl1,Bmx,Eln,Fbln2,Gkn3) found in the arteries were also present in all of our EC clusters showing no flow dependency.…”
Section: Accessibility and Co-accessibility Analyses Reveal Flow-depementioning
confidence: 72%
“…Our UMAP analysis identified 16 unique cell clusters distributed in a flow-and timedependent manner ( Figure 1A and B). Each cell cluster was identified using well-established marker genes ( Figure 1C) (Cochain et al, 2018;Kalluri et al, 2019;Roberts et al, 2020;Winkels et al, 2018). We found 8 endothelial cell clusters (E1-E8), vascular smooth muscle cells (SMCs), fibroblasts (Fibro), 4 monocytes/macrophages (M1-4), dendritic cells (DCs) and T-cells.…”
Section: Scrnaseq and Scatacseq Analyses Using The Mouse Pcl Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This arrangement allows the endothelium to detect and process multiple stimuli in parallel and to generate stimulusspecific responses [30][31][32][33] . These findings, together with studies that describe molecular [34][35][36][37][38][39][40][41] and functional heterogeneity 40,42 in endothelial cells across vascular beds, and within single vessel segments, raise the possibility that dysfunctional vascular responses could arise from altered endothelial cell heterogeneity and disrupted network dynamics. Indeed, altered mulitcellular network behavior underlies disease development in a variety of physiological systems.…”
Section: Introductionmentioning
confidence: 99%